2020
DOI: 10.1044/2019_lshss-ochl-19-0016
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Children With Hearing Loss on an Audiovisual Version of a Nonword Repetition Task

Abstract: Purpose The aims of this study were to (a) determine if a high-quality adaptation of an audiovisual nonword repetition task can be completed by children with wide-ranging hearing abilities and to (b) examine whether performance on that task is sensitive to child demographics, hearing status, language, working memory, and executive function abilities. Method An audiovisual version of a nonword repetition task was adapted and administered to 100 school-ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…In terms of children with normal hearing, some studies recruited age-and sex-matched controls (Surowiecki et al, 2002), while others included subjects' siblings to control sociodemographic factors that may have an effect on children's overall performance (Ead, Hale, DeAlwis, & Lieu, 2013). The allocation of children with both sensorineural and conductive hearing loss to the same group in one study (Al-Salim, Moeller, & McGregor, 2020) contrasts with the rest of the studies, which only focused on sensorineural hearing loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of children with normal hearing, some studies recruited age-and sex-matched controls (Surowiecki et al, 2002), while others included subjects' siblings to control sociodemographic factors that may have an effect on children's overall performance (Ead, Hale, DeAlwis, & Lieu, 2013). The allocation of children with both sensorineural and conductive hearing loss to the same group in one study (Al-Salim, Moeller, & McGregor, 2020) contrasts with the rest of the studies, which only focused on sensorineural hearing loss.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this systematic review indicate that children with deafness have a lower performance in hearing skills, from phonological discrimination to verbal reasoning, which are acquired later, regardless of whether the child had a cochlear implant or some other hearing aid. If stimuli are presented in a multiple-choice format or if recognition is limited to hearing, deaf children presented greater difficulties; however, if these were accompanied by visual clues, performance was improved (Al-Salim et al, 2020). Despite the use of cochlear implants or hearing aids, children with hearing loss do not have the same linguistic development as their hearing peers (Ambrose, Fey, & Eisenberg, 2012;Colin, Leybaert, Ecalle, & Magnan, 2013;Nittrouer et al, 2012).…”
Section: Discussion and Conclusion The Role Of Language In Overall Performance Of Children And Adolescents With Hearing Lossmentioning
confidence: 99%
“…Many studies on the CI population use large age spans and include pre-school children, school-aged children, adolescence and sometimes even adults in the same study (e.g. : Al-Salim et al, 2020;AuBuchon et al, 2019;De Giacomo et al, 2013;Kronenberger et al, 2014). Large age spans make it impossible to evaluate which age group is driving the differences.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, a significant contribution of phonological sensitivity to reading in advanced grades has been reported (Geers & Hayes, 2011). In addition, it has been found that sensitivity to phonological structure is important for novel word learning, as measured by nonword repetition (Al-Salim et al, 2020;Dillon & Pisoni, 2006;Nittrouer et al, 2014), and for the operations of the phonological loop in verbal working memory (Nittrouer et al, 2013). However, the role of this sensitivity to the recognition of continuous speech has not been previously evaluated.…”
Section: Why Malapropismsmentioning
confidence: 99%